2022
DOI: 10.3389/fped.2022.882056
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Pulmonary Ultrasound in Neonatal Ventilator-Associated Pneumonia

Abstract: This study explored the application value of lung ultrasound (LUS) in neonatal ventilator-associated pneumonia (NVAP). In this study, 122 newborns suspected of NVAP were treated in the NICU of Liaocheng People’s Hospital between July 1, 2020, and July 1, 2021. Of these, 115 were clinically diagnosed with NVAP. The diagnostic value of LUS for NVAP was determined by comparing the different signs of LUS and chest X-ray (CXR). The confirmed cases were divided into the failure and success groups according to the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…After admission, the physical examination, arterial blood gas analysis, routine blood tests, and coagulation function tests all gave normal results. Lung ultrasound (LUS) showed bilateral confluent B-lines, alveolar-interstitial syndrome, and subpleural consolidation with air bronchograms in some intercostal spaces, consistent with ultrasound image characteristics of neonatal pneumonia [6][7][8] (Figure 2A). The brain ultrasound images and cerebral hemodynamic monitoring were normal (Figure 3).…”
supporting
confidence: 60%
“…After admission, the physical examination, arterial blood gas analysis, routine blood tests, and coagulation function tests all gave normal results. Lung ultrasound (LUS) showed bilateral confluent B-lines, alveolar-interstitial syndrome, and subpleural consolidation with air bronchograms in some intercostal spaces, consistent with ultrasound image characteristics of neonatal pneumonia [6][7][8] (Figure 2A). The brain ultrasound images and cerebral hemodynamic monitoring were normal (Figure 3).…”
supporting
confidence: 60%
“…Jiang et al [ 41 ] conducted a study to compare CXR and LUS in 115 patients with ventilator-associated pneumonia (VAP). LUS findings of the confirmed cases showed a lung consolidation with an air bronchogram sign (111/115), alveolar-interstitial syndrome (113/115), pleural effusion (12/115), pleural line abnormalities (114/115), and lung pulse (15/115).…”
Section: Resultsmentioning
confidence: 99%
“…We found a meta-analysis assessing the role of LUS in diagnosing pneumonia in children < 16 years of age (a small number of infants included) [ 42 ]. Other smaller studies showed that LUS has excellent sensitivity and specificity for the diagnosis of severe pneumonia [ 39 ] and is more accurate than CXR for the diagnosis of VAP [ 41 ]. Moreover, some authors reported that adding LUS data to clinical features is more accurate than adding CXR data for the diagnosis of VAP [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The detailed characteristics of these studies are also presented in Table 2. Two studies were conducted in North America [14,29], sixteen in Europe [11][12][13]15,16,[18][19][20][21][22][23][24][26][27][28]35], seven in Asia [17,25,30,[32][33][34]36], and one in Africa [31]. The study subjects were mainly infants, children, and adolescents, except for two studies that included newborns [17,32].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Two studies were conducted in North America [14,29], sixteen in Europe [11][12][13]15,16,[18][19][20][21][22][23][24][26][27][28]35], seven in Asia [17,25,30,[32][33][34]36], and one in Africa [31]. The study subjects were mainly infants, children, and adolescents, except for two studies that included newborns [17,32]. A total of 23 studies involved pediatric patients admitted to either the wards or emergency departments, while three studies [15,17,32] involved patients in ICU (two studies in NICU and one in PICU).…”
Section: Study Characteristicsmentioning
confidence: 99%